Quality of Life in Patients with Chronic Heart Failure Under the Influence of Pharmacotherapy - Vakhidova Ikbolkhon Kholmurod qizi (Scholars Digest Publishing, 2023)
This article discusses chronic heart failure, which (CHF) is not an independent nosological form, but is a syndrome, a certain pathophysiological condition when dysfunction of the heart does not allow it to maintain the level of blood circulation necessary for tissue metabolism. Also, the course and prognosis of CHF, which largely depend on the characteristics of the underlying disease that caused it, such as ischemic heart disease, hypertension, heart defects and so-called non-coronary myocardial lesions (cardiomyopathies, myocarditis, etc.)
Keywords: chronic heart failure, methods of diagnosis and treatment, Quality of life, functioning in society, syndrome, pathophysiological condition, cardiac dysfunction.